Preliminary determination of wool quality of flock from the north area of La Pampa province (Veterinary Science, 2017)
Argentina counts on continuous introduction of sheep of different breed and/or types of animals, mainly wool farmers. Some areas of the country are characterized for having standardized the sheep while others have preserved the heterogeneity. Having in consideration that the north of La Pampa province was part of this process, and that there are not recent antecedent of the type of wool production of the flock, additionally to the existent of promotion laws that favoured new sheep farms, it was considered necessary to evaluate the existence genetic resources. A study was conducted to evaluate the sheep biotype in relation to wool production in order to know the quality of wool flocks distributed to the region. From 2011 to 2012 was develop a population survey of 8 flocks contained 1021 sheep of the north area of La Pampa. Morphology, conformation, coverage and colour phenotype were evaluated, and 400 wool samples were sent to the laboratory in order to be washed and classified by quality criteria as finesse (FM), type of fleece (TM) and bulk (BK). It was detected significant differences in classes of flock and wool type. In conclusion, the native sheep population of the north area of La Pampa produce wool of high quality for carpet purpose.
Keywords: Wool; Color; Type of fleece